Of Boldness and Badness: Insights into Workplace Malfeasance from a Triarchic Psychopathy Model Perspective - Neo, Bryan (Journal of business ethics, 2018)
Research has shown that individuals with high levels of psychopathic personality traits are likely to cause harm to others in the workplace. However, there is little academic literature on the potentially adaptive outcomes of corporate psychopathy, particularly because the “boldness” psychopathy domain has largely been under-acknowledged in this literature. This study aimed to elaborate on past findings by examining the associations between psychopathy, as operationalized using scales from the relatively new triarchic model of psychopathy (boldness, meanness, and disinhibition), and both adaptive and maladaptive workplace behaviors. Participants were 343 working community adults who completed a series of self-report questionnaires that measured psychopathy and various workplace behaviors, including counterproductive work behaviors (CWB), tactics of influence, unethical decision-making, leadership strategies, team play, and creativity. Structural equation modeling was used to estimate the associations between latent constructs of boldness, meanness, and disinhibition, and the eight different constructs related to workplace behaviors. It was found that boldness preferentially predicted the use of soft tactics of influence, adaptive leadership, and team play, and negatively predicted passive leadership. Meanness predicted unethical decision-making, poor team play, and hard tactics of influence. Disinhibition positively predicted CWB and passive leadership. Meanness also moderated the association between disinhibition and CWB, in that greater scores on both psychopathy domains indicated greater levels of CWB. These findings provide conceptual support for the triarchic model, including the “boldness” domain, which measures adaptive aspects of psychopathy in addition to maladaptive ones, as well as suggest that not all individuals high on psychopathy would be an overt menace to the workplace. The different psychopathy traits may also interact with each other to predict different types or levels of workplace behaviors.